Peers, Administration, and Mentor Support as Correlates of Completion/Non-Completion of Master’s and Doctoral Degrees among Muslim Educators - Derico-Lawi, Athena Jalaliyah B. (JPAIR Multidisciplinary Research, 2016)
Tertiary faculty members must finish their master’s degree in their field of specialization. However, many tertiary faculties have not been awarded master’s degrees or doctoral degrees because of non-completion of their thesis or dissertation. The study aimed to determine the relationship between the barriers in conducting thesis or dissertation and the completion/non-completion of master’s and doctoral degrees among Muslim educators who have completed their academic requirements. Purposive sampling was employed in the study. There were 60 participants of which 30 have completed their academic requirements for two years or more, and 30 participants have finished master’s and/or doctoral degrees for the purpose of comparison. Based on the results of the study, there is a significant relationship between the degree or course, employment status, faculty rank and number of years in service on the completion or non-completion of master’s or doctoral degrees. The participants were largely undecided as to the role of support system as a whole, but there is a significant relationship between peers, administration and mentor support on the completion or non-completion of master’s and doctoral degrees. The Mindanao State University system may adopt remedial measures to expose its faculty members and other academics to more research work that will improve their research skills.